Portuguese and Luso-Asian Legacies in Southeast Asia, 1511-2011, vol. 1 The Making of the Luso-Asian World: Intricacies of Engagement - Jarnagin, Laura (ISEAS Publishing, 2011)
After all, archives from all over the world, from Rio de Janeiro to London, from Lisbon to Rome, and from Goa to Macao, might still hold some secrets on the subject of Luso-Asian relations, when duly explored by resourceful scholars." - Rui M. Loureiro, Centro de Historia de Alem-Mar, Lisbon "This two-volume set pulls together several interdisciplinary studies historicizing Portuguese 'legacies' across Asia over a period of approximately five centuries (ca. 1511-2011). It is especially recommended to readers interested in the broader aspects of the early European presence in Asia, and specifically on questions of politics, colonial administration, commerce, societal interaction, integration, identity, hybridity, religion and language." - Associate Professor Peter Borschberg, Department of History, National University of Singapore